Respuesta :

( 5 - 2i ) ( 4 - i )       18 - 13i

( 2 - 5i ) ( 1 - 4i )     -18 - 13i

( 1 - 4i ) ( 5 - 2i )      -3 - 22i

( 4 + i ) ( 2 - 5i )     13 - 18i

Answer:

1) [tex](5-2i)(4-i)=18-13i[/tex]

2) [tex](2-5i)(1-4i)=-18-13i[/tex]

3) [tex](1-4i)(5-2i)=-3-22i[/tex]

4) [tex](4+i)(2-5i)=13-18i[/tex]    

Step-by-step explanation:

Given : Complex numbers

1) (5-2i)(4-i)

2) (2-5i)(1-4i)

3) (1-4i)(5-2i)

4) (4+i)(2-5i)

To find : The products of complex numbers with their standard forms.  

Solution :

We simply apply multiplicative property of brackets,

i.e, [tex](a+b)(c+d)=ac+bc+bc+bd[/tex]

Note - [tex]i^2=(\sqrt{-1})^2=-1[/tex]

1) (5-2i)(4-i)

[tex](5-2i)(4-i)=((5)(4)+(-2i)(4)+(-5)(i)+(-2i)(-i))[/tex]

[tex](5-2i)(4-i)=(20-8i-5i+2i^2)[/tex]

[tex](5-2i)(4-i)=(20-13i-2)[/tex]

[tex](5-2i)(4-i)=18-13i[/tex]

2) (2-5i)(1-4i)

[tex](2-5i)(1-4i)=((2)(1)+(-5i)(1)+(2)(-4i)+(-5i)(-4i))[/tex]

[tex](2-5i)(1-4i)=(2-5i-8i+20i^2)[/tex]

[tex](2-5i)(1-4i)=(2-13i-20)[/tex]

[tex](2-5i)(1-4i)=-18-13i[/tex]

3) (1-4i)(5-2i)

[tex](1-4i)(5-2i)=((5)(1)+(-4i)(5)+(-2i)(1)+(-2i)(-4i))[/tex]

[tex](1-4i)(5-2i)=(5-20i-2i+8i^2)[/tex]

[tex](1-4i)(5-2i)=(5-22i-8)[/tex]

[tex](1-4i)(5-2i)=-3-22i[/tex]

4) (4+i)(2-5i)  

[tex](4+i)(2-5i)=((4)(2)+(i)(2)+(4)(-5i)+(i)(-5i))[/tex]

[tex](4+i)(2-5i)=(8+2i-20i-5i^2)[/tex]

[tex](4+i)(2-5i)=(8-18i+5)[/tex]

[tex](4+i)(2-5i)=13-18i[/tex]                

Therefore, following above are the required results.